Comparative human-sensory evaluation and quantitative comparison of odour-active oxidation markers of encapsulated fish oil products used for supplementation during pregnancy and the breastfeeding period. - Sandgruber, Stefanie; Büttner, Andrea (Food Chemistry, 2012)
Three different commercial encapsulated fish oil supplements were evaluated by orthonasal sensory evaluation of the encapsulated oil samples, and were rated according to characteristic odour qualities and hedonic impact. The potent odourants of the fish oil samples were obtained by solvent extraction followed by high vacuum transfer of the volatiles, and were evaluated by means of high resolution gas chromatography-olfactometry (HRGC-O). Comparative aroma extract dilution analysis of the solvent extract samples revealed 40 odourants. Most of these were identified based on their respective retention indices on two capillaries of different polarities, their mass spectral data, as well as their odour characteristics during HRGC-O, in comparison with the respective reference compounds. Thereby (poly)unsaturated fatty acid oxidation products were demonstrated to play a significant role in the volatile fraction of the fish oil supplements. Quantification of selected oxidation marker substances confirmed predominant presence of these compounds in the investigated samples, but also major quantitative differences between samples with regard to specific compounds. These data may be used as the basis for future evaluation of sensory quality of encapsulated fish oil supplements, and might relate to the degree of acceptance or rejection by the mothers being supplemented with the respective products.<br